POTENSI CRYOPRESERVASION BENIH KOPI ARABIKA: PENGARUH POTENSIAL OSMOTIK DAN DURASI OSMOCONDITIONING TERHADAP VIABILITAS DAN INDEKS VIGOR HIPOTETIK BENIH - Yosefina Lewar; Maria Klara Salli; Olivina S. Messakh (Partner, 2008)
Cryopreservasion Potency of Coffea arabica Seed: Influence of Potential Osmotic and Osmoconditioning Duration to Viability and Hypothetic Vigor Index of Seed. This research aimed to prove the influence of potential osmotic and osmoconditioning to cure the seed viability and hypothetic vigor index of Coffea arabica as the result of draining or degradation of seed water until 12%. This research was an early step to test cryopreservasion potency of Coffea arabica seed, arranging factorially in Completely Randomized Design, consisting of two factors that are three potential osmotic levels (P): -0.5 Mpa; -1.0 MPa and -1.5 Mpa; and 3osmoconditioning duration level (D): 3, 5, and 7 days; and control (without osmoconditioning). Variables measured were electrical conductivity, free fat acid contents, radicel growth, time required for reaching 50% seed germination (T50), seed viability and hypothetic vigor index. Data obtained were analyzed using Analysis of Variance, and Duncan Multiple Range Test (DMRT) at 5%. The result indicated that potential osmotic -0.5 MPa of osmoconditioning performed best influence to T50. Potential osmotic of -1.5 MPa presented best effect to seed viability and hypothetic vigor index. Five days Osmoconditioning performed best influence to time T50. Potential osmotic -0.5 MPa of 3-days osmoconditioning presented best influence to free fat acid contents and seed viability. Potential osmotic -0.5 MPa of 5-days osmoconditioning performed best influence to free fat acid contents and radicel growth. Potential osmotic -1,0 MPa and 5-days osmoconditioning were best affected to seed viability; while, potential osmotic -1.5 MPa of 5-days osmoconditioning also performed best influence to seed viability, and potential osmotic -1.5 MPa of 7-days were significant to seed viability and electrical conductivity of Coffea arabica.Keywords: cryopreservasion, potential osmotic, osmoconditioning duration, Coffea arabica